A imagem improvável do escritor: Raymundo de Souza Dantas - apontamentos sobre a vida e obra - Marina Luiza Horta Silva (2015)
In contrast to the critical importance and popularity that some authors have among academics, the pages in Raymundo Souza Dantas' books remain, more than half a century after their release, virtually closed to literary criticism. The main objective of this Master thesis is to put in evidence texts which stage the reflections of a young writer who is conscious of his barely improbable projection in the literary space - since he was a newly literate black man of humble origins. This objective will be pursued through the reading of Dantas' autobiographic books 'Um começo de vida', 'Reflexões dos 30 anos' and 'África Difícil': missão condenada as well as his fiction narratives, 'Solidão nos campos' and 'Agonia'. In these books, the inscription of the author is perceived both in the construction of an image of the writer and in the fictional creation. The theories of biographical criticism and Afro-Brazilian literature will be used in order to demonstrate how such inscription traces a literary project which remarkably reveals the silencing and marginalization of the black subject in the Brazilian political and literary scenes during the first half of the 20th century.